Unusual enhancement in efficiency of DSSCs upon modifying photoanodes with reduced graphene oxide. Issue 46 (20th October 2022) - Bhand, Sujit; Jha, Plawan Kumar; Ballav, Nirmalya
Abstract : Reduced graphene oxide (rGO) has emerged as an excellent interfacial material for improvising the performance of dye-sensitized solar cells (DSSC). Abstract : Reduced graphene oxide (rGO) has emerged as an excellent interfacial material for improvising the performance of dye-sensitized solar cells (DSSC). Herein, we have applied rGO as interfacial layers between a fluorine doped tin oxide (FTO) coated glass substrate and semiconducting material TiO2 in a photoanode of a DSSC which showed an unusual enhancement in generating a photocurrent in comparison to the control (without rGO layers). An electrochemical impedance spectroscopy (EIS) study was performed to gain the mechanistic insights into such a remarkable enhancement of photoelectric conversion efficiency (PCE) which revealed improved charge transfer and suppressed charge recombination due to high-electrical conductivity and probably more negative work function of our rGO material compared to the bare TiO2 photoanode.